Clinical and epidemiological characteristics of atrial fibrillation in patients from the Regional Hospital of Ica - Dávila-Hernández, Carlos Alberto (2019)
OBJECTIVE. To determine the clinical epidemiological characteristics of patients with atrial fibrillation (AF) who attended the Regional Hospital of Ica between 2012 and 2015. MATERIAL AND METHODS. A descriptive, retrospective and transversal study was carried out; In 203 patients diagnosed with CIE 10 I48.X, I49.0-I49.9 who were treated in the cardiology and internal medicine service. The data were obtained from the review of medical records. RESULTS. Atrial fibrillation occurs at a rate of 4 per 1000 patients. The mean age was 72 year-old (range: 45-104 yr). Fifty four per cent was male. AF with controlled ventricular rate was 52 %, with high ventricular rate 47 %. Abnormal ECG was found in 74 %; overweight 70 %; arterial hypertension 60 %; diabetes mellitus 36 %; acute myocardial infarction 22 %; smoking 12 %. Mortality was reported in 6,4 %. CONCLUSIONS. Four out of 1 000 people were found to have atrial fibrillation. Old age and comorbidities were frequent.